The “ POWERS ” Heuristic: Key Considerations for Enhancing Implementation Readiness in Pharmacy Practice and Beyond - Melanie Livet (JACCP: JOURNAL OF THE AMERICAN COLLEGE OF CLINICAL PHARMACY, 2026)
ABSTRACT Effective implementation of pharmacist‐delivered patient care interventions requires systematic, careful pre‐launch planning, which includes assessing and building readiness of the health care setting embracing this change. A health care team needs to be both willing and able to deliver the selected service. Despite its recognized importance, implementation readiness has rarely been operationalized into a usable system for pharmacy practice. The present article introduces the “POWERS” heuristic, which outlines the six elements of implementation readiness to consider in preparation for service implementation: Ready patient ( P atient), Ready priorities ( O rganizational Priorities), Ready workflow ( W orkflow), Ready workforce ( E ngaged Workforce), Ready Operations ( R esources and Operations), and Ready Supports ( S upports). These domains represent the readiness content components of a broader readiness formula that, when paired with a systematic readiness assessment and building (RAB) process, provides a structured approach to strengthening implementation readiness. Application of the heuristic within the RAB process is illustrated through a case study involving delivery of three community pharmacist‐delivered patient care services (for diabetes, cardiovascular disease, and anxiety/depression) in 22 national/regional, grocery store, and independently owned pharmacies. This heuristic not only expands on current conceptualizations of readiness, but also provides a practical and actionable set of readiness domains to support systematic readiness assessment and building efforts in pharmacy practice and beyond.